Socio-spatial relations and the governance of city-regional growth: A comparative analysis of two European high-tech regions - Ganser, Robin; Valler, Dave (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Oxford-Oxfordshire, UK, and the Verband Region Stuttgart or the Metro Region in Germany are two of Europe’s high-tech powerhouses, facing similar challenges concerning housing and infrastructure provision and accommodating regional as well as local economic growth. Based on desktop studies and semi-structured expert interviews, this paper examines the respective institutional, political and cultural contexts for strategic planning in the two distinct settings, aiming to identify the evolving balance of socio-spatial dimensions influencing each case. While the interplay of territory, place, scale and network is different across the two cases, both face ongoing dilemmas. In the Stuttgart region, an established and smoothly running economic and spatial growth-machine has stuttered as growth has reached capacity and localities have asserted their constitutional controls on urban expansion. In Oxford (and the wider county of Oxfordshire), there has been a contrasting dislocation between an emerging growth agenda and a fractured governance context that is historically less oriented towards growth. Additionally, Oxfordshire has operated since 2010 against the background of localism in English planning and an increasing reliance on city and housing/growth ‘deals’ negotiated with central government to access planning flexibilities and infrastructure funding. Conclusions are drawn with the aim of mutual learning from the different international experiences and of informing approaches to strategic and inter-municipal planning.